Resepsi Fungsional Al-Quran dalam Tradisi Nariyahan di PP. Putri Mahyajatul Qurro' Kunir, Wonodadi Blitar - Nadhiroh, Lailatun; Aini, Adrika Fithrotul (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
Functional Reception of the Quran is a study of living Quran that discusses the acceptance and response of the community to an action or tradition which is then associated with the Quran. This paper aims to explain the functional session of the Quran contained in the Nariyahan tradition in PP. Putri Mahyajatul Qurro' Kunir Wonodadi Blitar. This article uses a descriptive-qualitative method with an emic approach to the study of living Quran also focuses on the sociological theory offered by Peter L. Berger with social construction analysis. From this research, it can be seen that there are three moments in interpreting a tradition, which: (1) The moment of externalization, because it is factored by the rules of caregivers, which directs the students to follow this series of Nariyahan traditions carefully, they experience adjustments in carrying out the series of traditions; (2) The moment of objectivation of the students experiencing awareness of the advice to support, follow, live and believe that there is faḍilah in each of these traditional compositions. In addition, in the implementation of this reception they also realized that this practice is a form of effort to get the pleasure of Allah SWT. so that they gain wisdom for what they do; and (3) In the moment of internalization, each individual has a varied point of view in interpreting the functional reception of the Qur'an in the tradition. For example, gaining peace of mind, disciplining yourself, actively worshiping, increasing diligent in studying, getting blessings and the pleasure of teachers, solution providers and much more.